17.2k views
0 votes
Let f (x) = –x2 + 3x + 1 and g(x) = 2x. Look at the composition shown. What is the error in the student’s work? f (g (x)) = –(2x)2 + 3x + 1 = –4x2 + 3x + 1

2 Answers

3 votes

in term 3x, the correct is 3(2x)

User Tony Baby
by
5.4k points
5 votes

Answer:

The error he did was that in place of 3(2x) he wrote 3x

i.e. the error was in the second term of the expression.

Explanation:

We are given that:

f (x) = -x² + 3x + 1 and g(x) = 2x

f(g(x))=f(2x)

= -(2x)²+3(2x)+1

= -4x²+6x+1

But, student wrote it as:

f (g (x)) = -(2x)² + 3x + 1 = -4x² + 3x + 1

On comparing our work with the students work, we see that

The error he did was that in place of 3(2x) he wrote 3x

i.e. the error was in the second term of the expression.

User Lautaro Cozzani
by
5.8k points